Tungsten alloy wire and product and preparation method thereof
By using a self-lubricating composite plating layer on the tungsten alloy wire, the problems of poor adhesion of graphite layer and insufficient adhesion of electroplating layer during the refining of traditional tungsten alloy wires are solved, and lower mold loss and higher yield are achieved.
Patent Information
- Application Number
- CN202411625536.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-14
AI Technical Summary
During the refining process of traditional tungsten alloy wire, poor adhesion of graphite layer, excessive graphite powder particle size leads to a decrease in lubricity, increased mold loss and low yield, and the adhesion of the electroplating layer on the surface of the tungsten substrate is insufficient.
Self-lubricated composite plating, including pre-plating and composite plating, pre-plating is metal chromium, composite plating is copper-based composite plating, containing solid lubricant molybdenum disulfide, the electroplating layer is enhanced by ultrasonic electrolytic alkali washing and hydrofluoric acid activation treatment. Adhesion.
It effectively reduces mold loss during the drawing process, improves the yield rate, enhances the bonding force between the electroplating layer and the tungsten alloy busbar, and avoids wire breakage or silicon wafer scratches caused by the plating layer falling off.
Smart Images

Figure CN119465323A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of diamond wires, and in particular relates to a tungsten alloy wire and a product thereof and a preparation method thereof. Background Art
[0002] Due to the advantages of low loss, low TTV, and high cutting efficiency, wire saw cutting is widely used in the cutting of hard and brittle materials such as monocrystalline silicon, polycrystalline silicon, and glass in the photovoltaic, semiconductor information, and LED industries. Wire saw cutting methods are divided into free mortar cutting and fixed abrasive cutting. Free mortar cutting uses bare metal wire to enter the slurry containing silicon carbide abrasives, and cuts by rolling extrusion grinding. This cutting method has problems such as low cutting efficiency and mortar pollution of the environment, and has gradually been replaced by fixed abrasive cutting methods. Fixed abrasive cutting wires are divided into electroplated diamond wire saws and resin diamond wire saws. Resin diamond wires have problems such as the loose bonding between the diamond abrasive and the wire core, and the diamond is easy to fall off during the cutting process. Therefore, the mainstream product on the market is electroplated diamond wire saws.
[0003] Electroplated diamond wire saw is a method of depositing diamond on a metal busbar by electroplating. According to the different metal busbars, it is divided into high-carbon steel diamond wire and tungsten alloy wire diamond wire. In order to reduce non-silicon costs and achieve grid parity, the photovoltaic industry will develop in the direction of thinning the electroplated diamond wire. The theoretical limit of the wire diameter of high-carbon steel diamond wire is about 30µm. Tungsten alloy wire has the advantages of high strength, high temperature resistance, and corrosion resistance. Tungsten alloy wire doped with rare earth elements has good processing performance. The theoretical limit of the wire diameter is about 22µm, which makes up for the shortcomings of carbon steel wire in terms of wire diameter, tensile strength, and corrosion resistance.
[0004] The traditional method of refining tungsten alloy wire is to cover the surface of tungsten alloy wire with graphite emulsion by spraying, and then heat and dry it, so that a graphite layer with good lubrication performance is formed on the surface of the wire, which allows the drawing process to continue. However, the difference in raw material selection among different manufacturers leads to large differences in graphite emulsion particle size, suspension, viscosity and other aspects. At the same time, the particle size of graphite powder in the fine wire graphite emulsion of most domestic manufacturers is >3µm. When the particle size of graphite powder is too large, when drawing 30-50µm fine wires, the lubricity of the graphite layer will decrease, increase mold loss and affect the yield of tungsten alloy wire. By using composite electroplating, a metal lubrication layer with fine crystallization, firmness and solid lubrication particles is electroplated on the surface of thick wire tungsten alloy wire, which can solve the problems of poor adhesion of traditional graphite layer and excessive graphite powder particle size, reduce mold loss and improve yield. However, metal tungsten is very active. Under oxygen-containing conditions, a dense black-blue passivation film is easily formed on the surface of tungsten alloy wire, which has high chemical stability. During electroplating, the presence of this passivation film usually results in a weak bond between the plated metal and the tungsten alloy busbar. On the other hand, when preparing diamond wire saws by composite electroplating, the metal tungsten alloy substrate and the electroplated nickel layer are also weakly bonded when electroplating with nickel sulfamate electroplating solution. Therefore, it is necessary to select appropriate pre-treatment methods and electroplating processes to solve the problem of adhesion of the electroplated layer on the surface of the tungsten substrate. Summary of the invention
[0005] In order to overcome the deficiencies of tungsten alloy busbars and diamond wires prepared by the prior art in terms of yield, mold loss, coating bonding strength, etc., the present invention provides a tungsten alloy wire and its products and a preparation method.
[0006] The first technical solution provided by the present invention is: a tungsten alloy wire, which is composed of a tungsten alloy busbar and a self-lubricating composite coating, wherein the self-lubricating composite coating is a pre-coating and a composite coating from the inside out. The tungsten alloy busbar is composed of metal tungsten and rare earth elements, the metal tungsten element accounts for more than 80%, and the rare earth element accounts for more than 0.1%. The proportion of the metal tungsten element can be 85%, 90%, 95%, 97%, 99% and all ranges and sub-ranges between the above values; the rare earth element accounts for 0.1%, 0.2%, 0.5%, 0.8%, 1.1%, 1.4% and all ranges and sub-ranges between the above values. Rare earth elements can refine tungsten grains in tungsten alloy wires and play a role in dispersion strengthening, thereby improving the tensile strength of the tungsten alloy wire itself. In addition, the rare earth elements in tungsten alloy wire are one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, yttrium and the like.
[0007] The wire diameter of the tungsten alloy wire is 10-200µm, and the tensile strength is above 3000MPa. Furthermore, the wire diameter of the tungsten alloy wire is 10µm, 15µm, 20µm, 25µm, 30µm, 35µm, 40µm, 45µm, 50µm, 55µm, 60µm, 65µm, 70µm, 75µm, 80µm, 85µm, 90µm, 95µm, 100µm, 105µm, 110µm, 115µm, 120µm, 125µm, 130µm, 135µm, 140µm, 145µm, 150µm, 155µm, 160µm, 165µm, 170µm, 175µm, 180µm, 185µm, 190µm, 195µm, 200µm and all ranges and sub-ranges between the above values. The tensile strength of the tungsten alloy wire is 3000 MPa, 3050 MPa, 3100 MPa, preferably 3200 MPa, and most preferably 3300 MPa.
[0008] The pre-plating layer is a metal chromium plating layer, and the single-side thickness is 0.1-1µm; the composite plating layer is a metal-based composite plating layer, and the single-side thickness is 0.1-5µm. Further, the single-side thickness of the pre-plating layer is 0.1µm, 0.2µm, 0.3µm, 0.4µm, 0.5µm, 0.6µm, 0.7µm, 0.8µm, 0.9µm, 1µm and all ranges and sub-ranges between the above values; the composite plating layer is one or more of the metal-based composite plating layers such as copper-based composite plating, tin-based composite plating, lead-based composite plating, zinc-based composite plating, nickel-based composite plating, iron-based composite plating, and cobalt-based composite plating, preferably a copper-based composite plating. Metal copper has good thermal conductivity and electrical conductivity, and has the characteristics of low hardness and good ductility. During the tungsten alloy wire drawing process, it can be deformed simultaneously with the wire. The single-side thickness of the composite coating is 0.1µm, 0.5µm, 1µm, 1.5µm, 2µm, 2.5µm, 3µm, 3.5µm, 4µm, 4.5µm, 5µm and all ranges and sub-ranges between the above values. Within this coating thickness range, the tungsten alloy wire can be completely covered by the electroplating layer and has good drawing performance.
[0009] The composite coating contains a solid lubricant, and the content of the solid lubricant in the metal-based composite coating is 0.1-10wt%. Further, the content of the solid lubricant in the metal-based composite coating is 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt% and all ranges and sub-ranges between the above values.
[0010] The particle size of the solid lubricant is 2-10µm. For example, the particle size of the solid lubricant can be 2µm, 3µm, 4µm, 5µm, 6µm, 7µm, 8µm, 9µm, 10µm and all ranges and sub-ranges between the above values. Within this particle size range, the solid particles can be uniformly dispersed in the plating solution.
[0011] The solid lubricant is composed of 0-100 wt% metal compound, 0-100 wt% inorganic matter and 0-100 wt% organic matter, wherein the metal compound includes one or more of metal oxide, metal halide, metal sulfide and metal selenide; the inorganic matter is one or more of graphite, graphite fluoride and hexagonal boron nitride; the organic matter is one or more of polytetrafluoroethylene, polyimide, nylon, polyethylene and melamine urate. In some preferred embodiments, the solid lubricating particles are molybdenum disulfide. Molybdenum disulfide has a hexagonal layered structure similar to graphite, and each unit layer is composed of three plane layers of S-Mo-S stacked together. The sulfur atoms are connected to the corresponding molybdenum atoms by strong covalent bonds and surround the molybdenum in the center like a triangular prism. The distance between the unit layers is 0.625nm, and the van der Waals force between adjacent layers is weak, which greatly reduces the shear force during the dislocation sliding between the layers, so molybdenum disulfide has very excellent solid lubrication properties. In addition, molybdenum disulfide has good corrosion resistance and conductivity, and its operating temperature in the atmospheric environment can reach 350°C, so it can exist stably in the electroplating solution. At the same time, under the action of the electric field force, it can be complexed with the metal ions in the plating solution and deposited on the tungsten alloy wire.
[0012] Further, the metal oxide is one or more of metal oxides such as lead oxide, copper oxide, zinc oxide, tin oxide, and molybdenum oxide; the metal sulfide is one or more of metal sulfides such as molybdenum disulfide, tungsten disulfide, iron sulfide, and chromium sulfide; the metal halide is one or more of metal halides such as calcium fluoride, barium fluoride, and lanthanum fluoride; the metal selenide is niobium diselenide; the inorganic solid lubricant is one or more of inorganic substances such as graphite, graphite fluoride, and hexagonal boron nitride; the organic solid lubricant is one or more of organic solid lubricants such as polytetrafluoroethylene, polyimide, nylon, polyethylene, and melamine urate. Preferably, the solid lubricant is composed of 50-80 wt% of metal compounds, 1-30 wt% of inorganic substances, and 1-30 wt% of organic substances; more preferably, the solid lubricant is composed of 70-80 wt% of metal compounds, 5-20 wt% of inorganic substances, and 5-20 wt% of organic substances.
[0013] The present invention also provides a method for preparing the aforementioned tungsten alloy wire, comprising the following steps: Step 1: Pre-treat the tungsten alloy busbar; Step 2: electroplating, placing the tungsten alloy busbar obtained in step 1 in an electroplating tank for pre-plating of the bottom metal coating, and then electroplating the composite coating in the electroplating tank. After the electroplating is completed, the tungsten alloy busbar is washed and soap-soaked, and then wound onto the I-shaped wheel; Step 3: Drawing, install the tungsten alloy busbar obtained in step 2 at the wire-paying end of the water tank drawing machine, and the tungsten alloy wire reaches the required wire diameter after multiple drawing passes. Preferably, the outlet die in the drawing machine uses a natural diamond die, which can improve the surface quality of the tungsten wire and reduce the ovality of the tungsten wire.
[0014] The detailed steps of the pre-treatment in step 1 are: Step A, place the tungsten alloy busbar in an ultrasonic electrolytic alkaline washing tank for cleaning, and then wash it with water, pickle and wash it with water in three steps. The alkaline solution is composed of one or more of sodium hydroxide, sodium carbonate and trisodium phosphate, the concentration of the alkaline solution is 50-150g / L, the temperature is 50-80°C, the degreasing time is 1-5s, and the ultrasonic frequency is 10-100Hz; tungsten alloy wire has good corrosion resistance, is insoluble in strong acids such as hydrochloric acid, sulfuric acid and nitric acid at room temperature, and is only soluble in a mixed acid of hydrofluoric acid and concentrated nitric acid. After the tungsten alloy wire is oxidized, the tungsten oxide formed on the surface is easily soluble in alkaline solution. Usually, after the tungsten alloy wire is drawn with graphite emulsion, graphite and organic solvents may still remain on the surface. Therefore, it is necessary to remove the impurities such as oxide scale, graphite emulsion and organic solvent remaining on the surface of the tungsten alloy busbar by anodic oxidation of the tungsten alloy busbar and then dissolving it in alkaline solution. The water washing is a two-stage water washing method, which adopts a countercurrent water washing method. After the tungsten alloy busbar is electrolyzed, it first enters the hot water washing tank, then enters the acid washing activation tank after passing through the cold water washing tank, and is cleaned again with deionized water before entering the electroplating tank. The activation mechanism in the pre-treatment and electroplating process of the present invention is: hydrofluoric acid is highly corrosive. Through the strong chemical corrosion of hydrofluoric acid, the passivation film on the surface of the tungsten alloy busbar is removed, and the surface of the tungsten alloy busbar is coarsened. There are gaps between the grains of the tungsten alloy busbar, and some are in the shape of barbs. When electroplating on such a surface, the chromium layer will be firmly self-locked on the surface of the tungsten alloy busbar, thereby enhancing the bonding force between the chromium plating layer and the tungsten alloy busbar. At the same time, metal chromium and tungsten have the same body-centered cubic structure and similar thermal expansion coefficients, so chromium is selected as the pre-plating layer. When preparing a diamond wire saw, impact nickel is used for pre-plating. During the pre-plating process, hydrogen with strong reducing properties is precipitated on the cathode wire body, which plays a role in further activating the metal surface.
[0015] Step B, two-stage water washing, using countercurrent water washing method, after degreasing, the tungsten alloy busbar first enters the hot water washing tank, the water temperature is 50-70℃, the time is 1-5S, and then passes through the cold water washing tank; Step C: Activate the surface of the tungsten alloy busbar with concentrated hydrochloric acid or hydrofluoric acid at a temperature of 10-30°C for 1-5 seconds, and then wash with water for activation.
[0016] The process of pre-plating the bottom metal layer in step 2 is: the current density is 4-20A / dm 2 , the plating time is 1-30S; the anode is a lead-tin alloy or a platinum-iridium anode; the plating solution composition is chromic anhydride: 100-400g / L, sulfuric acid 1-5g / L, La 3+ : 0.1-2.5g / L.
[0017] The process of electroplating the composite coating in step 2 is as follows: the electroplating solution composition is 250g / L of one or more of metal oxides, metal halides, metal sulfides, metal selenides, 100g / L of sulfuric acid, and 0.1-100g / L of solid lubricant; the current density is 8-10A / dm 2 The solid lubricant has a concentration of 0.1-100 g / L in the electroplating solution. For example, the solid lubricant concentration is 0.1 g / L, 0.5 g / L, 0.8 g / L, 1 g / L, 5 g / L, 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L and all ranges and sub-ranges between the above values. Within this concentration range, the lubricating coating has a high particle content and good lubricity.
[0018] The present invention also provides a diamond wire saw made of the aforementioned tungsten alloy wire and a preparation method thereof, wherein the aforementioned tungsten alloy wire is subjected to alkali washing and acid washing pre-treatment according to the prior art, and after being primed with impact nickel, the diamond wire saw is prepared by composite electroplating. Preferably, the acid washing uses one or more of aminosulfonic acid, hydrochloric acid or sulfuric acid. The components of the impact nickel plating solution are nickel chloride: 200-300g / L, hydrochloric acid: 100-200ml / L, and the current density is 1-15A / dm 2 , the plating time is 5-15s, and the plating solution temperature is 15-35℃.
[0019] The beneficial effects of the present invention are as follows: on the one hand, the tungsten alloy busbar is etched by hydrofluoric acid, and a pre-plated bottom layer is added at the same time, thereby enhancing the bonding strength between the electroplated layer and the tungsten alloy busbar. At the same time, a lubricating composite coating is prepared by adding solid lubricating particles to the electroplating solution for composite electroplating, thereby effectively reducing the mold loss during the drawing process and saving costs; on the other hand, the pre-plating process of nickel sulfamate is changed, and impact nickel is used as the pre-plated bottom layer of the diamond wire, thereby enhancing the bonding strength between the grinding composite coating and the diamond wire busbar, thereby preventing problems such as wire breakage or silicon wafer scratches caused by the shedding of the grinding composite coating during the cutting process of the diamond wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the cross section of the tungsten alloy wire of the present invention; Figure 2 This is a process flow chart of manufacturing tungsten alloy wire of the present invention; Figure 3 The present invention is a manufacturing process flow chart of the diamond wire saw; Figure 4 This is a scanning electron microscope image of the product prepared in Example 1 of the present invention; Figure 5 This is a scanning electron microscope image of the product prepared according to Comparative Example 1 of the present invention; Figure 6 This is a scanning electron microscope image of the product prepared in Example 2 of the present invention.
[0021] Among them: 1- tungsten alloy wire, 2- pre-plated metal layer, 3- self-lubricating composite coating. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In some embodiments, the tungsten alloy wire contains metal tungsten and rare earth elements. The proportion of metal tungsten is more than 80%, and the proportion of rare earth elements is more than 0.1%. For example, the proportion of metal tungsten can be 85%, 90%, 95%, 97%, 99%, etc.; the proportion of rare earth elements is 0.2%, 0.5%, 0.8%, 1.1%, 1.4%, etc. Rare earth elements can refine tungsten grains in tungsten alloy wires and play a role in dispersion strengthening, thereby improving the tensile strength of the tungsten alloy wire itself. In addition, the rare earth elements in the tungsten alloy wire are one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, yttrium and other elements.
[0024] In some embodiments, the pre-plated metal layer is a metal chromium layer, which is pre-plated by impact electroplating, and the thickness of a single side is 0.1-1 μm. Metal chromium and tungsten have the same body-centered cubic structure and similar thermal expansion coefficients. When electroplated by impact, hydrogen with strong reducing properties is precipitated on the cathode line, which further activates the metal surface, so that the chromium layer and the tungsten alloy substrate have a strong bonding force.
[0025] In some embodiments, the composite coating containing lubricating particles is one or more of a copper-based composite coating, a tin-based composite coating, a lead-based composite coating, a zinc-based composite coating, a nickel-based composite coating, an iron-based composite coating, a cobalt-based composite coating, etc. In some preferred embodiments, the composite coating containing solid lubricating particles is a copper-based composite coating. Metallic copper has good thermal and electrical conductivity, low hardness, good ductility, etc., and can be deformed simultaneously with the wire during the drawing process of the tungsten alloy wire.
[0026] In some embodiments, the solid lubricant particles of the composite coating include metal compounds, inorganic substances, organic substances and the like. The metal compounds in the solid lubricating particles include one or more of metal compounds such as metal oxides, metal halides, metal sulfides, and metal selenides. The metal oxides are one or more of metal oxides in lead oxide, copper oxide, zinc oxide, tin oxide, molybdenum oxide, etc.; the metal sulfides are one or more of metal sulfides such as molybdenum disulfide, tungsten disulfide, iron sulfide, and chromium sulfide; the metal halides are one or more of metal halides such as calcium fluoride, barium fluoride, and lanthanum fluoride; the metal selenide is niobium diselenide; the inorganic solid lubricant is one or more of inorganic substances such as graphite, graphite fluoride, and hexagonal boron nitride; the organic solid lubricant is one or more of organic solid lubricants such as polytetrafluoroethylene, polyimide, nylon, polyethylene, and melamine urate. In some preferred embodiments, the solid lubricating particles are molybdenum disulfide. Molybdenum disulfide has a hexagonal layered structure similar to graphite. Each unit layer is composed of three superimposed plane layers of S-Mo-S. The sulfur atoms are connected to the corresponding molybdenum atoms by strong covalent bonds, and surround the molybdenum in the center like a triangular prism. The distance between unit layers is 0.625nm, and the van der Waals force between adjacent layers is weak, which greatly reduces the shear force during the dislocation sliding between the layers. Therefore, molybdenum disulfide has very excellent solid lubrication properties. In addition, molybdenum disulfide has good corrosion resistance and conductivity. The operating temperature in the atmospheric environment can reach 350°C, so it can exist stably in the electroplating solution. At the same time, under the action of the electric field force, it is compounded with the metal ions in the plating solution and deposited on the tungsten alloy wire.
[0027] In some embodiments, the thickness of the self-lubricating composite coating is 0.5-5 μm. For example, the thickness of the self-lubricating composite coating can be 0.8 μm, 1.6 μm, 3.2 μm, 4.8 μm, etc. Within this coating thickness range, the tungsten alloy busbar can be completely covered by the electroplating layer, and the drawing performance is good.
[0028] In some embodiments, the particle size of the solid lubricant is between 2-10 μm. For example, the particle size of the solid lubricant may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, etc. Within this particle size range, the solid particles can be uniformly dispersed in the plating solution.
[0029] In some embodiments, the solid lubricant has a concentration of 0.1-100 g / L in the electroplating solution. For example, the solid lubricant concentration is 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, etc. Within this concentration range, the lubricating coating has a high particle content and good lubricity.
[0030] like Figure 2 and Figure 3 As shown, in some embodiments, a method for preparing a tungsten alloy wire and a diamond wire comprises the following steps: Step 1: Pre-treat the tungsten alloy busbar after electrolytic cleaning.
[0031] The pre-treatment step in step one is to put the tungsten alloy busbar from the wire-releasing end into the ultrasonic electrolysis alkaline washing tank, and then enter the electroplating tank after three steps of water washing, acid washing and water washing. Tungsten alloy wire has good corrosion resistance. It is insoluble in strong acids such as hydrochloric acid, sulfuric acid, and nitric acid at room temperature. It is only soluble in a mixed acid of hydrofluoric acid and concentrated nitric acid. After the tungsten alloy wire is oxidized, the tungsten oxide formed on the surface is easily soluble in alkaline solution. Usually, after the tungsten alloy wire is drawn with graphite emulsion, graphite and organic solvents may still remain on the surface. Therefore, it is necessary to remove the impurities such as oxide scale, graphite emulsion and organic solvent remaining on the surface of the tungsten alloy busbar by anodic oxidation and dissolving it in alkaline solution. The water washing is a two-stage water washing method, which adopts a countercurrent water washing method. After the tungsten alloy busbar is electrolyzed, it first enters the hot water washing tank, then enters the acid washing activation tank after passing through the cold water washing tank, and is washed again with deionized water before entering the electroplating tank.
[0032] In some embodiments, the alkali solution composition is one or more of sodium hydroxide, sodium carbonate, and trisodium phosphate, the alkali solution concentration is 50-150g / L, the temperature is 50-80°C, the oil removal time is 1-5s, and the ultrasonic frequency is 10-100Hz; the water temperature of the washing tank after electrolytic cleaning is 50-70°C, and the time is 1-5S.
[0033] In some embodiments, the acid solution uses concentrated hydrochloric acid or hydrofluoric acid to activate the surface of the tungsten alloy busbar, and the acid solution temperature is 10-30° C. and the time is 1-5S.
[0034] In some embodiments, the impact chromium plating solution comprises chromic anhydride: 100-400 g / L, sulfuric acid 1-5 g / L, La 3+ :0.1-2.5g / L Current density is 4-20A / dm 2 The electroplating time is 1-30S, and the anode is a lead-tin alloy or a platinum-iridium anode.
[0035] Step 2: Electroplating self-lubricating composite coating. After activated water washing, the tungsten alloy busbar enters the electroplating tank for pre-plating of the bottom metal coating, and then enters the electroplating tank for electroplating of the lubricating composite coating. After the electroplating is completed, the wire is washed, dried, and soap-soaked, and the servo motor is used to reel the wire onto the I-shaped wheel at a certain pitch.
[0036] In some preferred embodiments, the lubricating composite coating is a copper-based composite coating, and the solid lubricant is molybdenum disulfide. The plating solution contains 200-300 g / L copper sulfate and 100-200 g / L sulfuric acid, the temperature is 10-30°C, and the current density is 5-20 A / dm 2 The wire is dried in a heating furnace at a temperature of 200-300°C for 1-5 seconds. After the wire is soaked in soap, a lubricating film can be formed on the surface to prevent oxidation of the steel wire surface, which is beneficial for wire arrangement at the take-up end and subsequent drawing.
[0037] Step 3: Drawing, install the electroplated tungsten alloy wire on the wire pay-off end of the water tank drawing machine, and the alloy wire diameter reaches the required wire diameter after multiple die drawing; In some embodiments, the outlet mold is a natural diamond mold, which can improve the surface quality of the tungsten wire and reduce the ovality of the tungsten wire.
[0038] To prepare the tungsten alloy wire product of the present invention, specifically, to prepare a diamond wire saw, the drawn tungsten alloy wire is subjected to alkali washing, water washing, and acid washing pretreatment, and then subjected to impact nickel priming, and then the diamond wire saw is prepared by composite electroplating. The acid washing uses one or more of aminosulfonic acid, hydrochloric acid, or sulfuric acid. The impact nickel plating solution is composed of nickel chloride: 200-300g / L, hydrochloric acid: 100-200ml / L, and the current density is 1-15A / dm 2 The electroplating time is 5-15s, the electroplating solution temperature is 15-35℃, and the single-side coating thickness is 0.1-1μm. Example
[0039] This embodiment provides a method for preparing a tungsten alloy wire and a product thereof Step 1: The tungsten alloy busbar enters the ultrasonic electrolytic alkali washing tank from the pay-off end. The alkali solution is composed of sodium hydroxide, the concentration is 70g / L, the alkali solution temperature is 70℃, the alkali washing time is 5s, and the ultrasonic frequency is 25HZ. After degreasing, the tungsten alloy busbar enters the hot water and cold water secondary washing tank, and the alkali solution on the surface of the tungsten wire is completely cleaned by countercurrent. The hot water washing temperature is 60℃ and the cold water washing temperature is 25℃. After washing, the tungsten alloy busbar enters the pickling activation tank and is etched and activated with hydrofluoric acid. The hydrofluoric acid concentration is 20%, the temperature is 25℃, and the activation time is 3s.
[0040] Step 2: Electroplating is performed after pretreatment. First, metal chromium is pre-plated on the surface of the tungsten alloy busbar as the bottom bonding layer. The impact chromium anode is a lead-tin alloy, and the electroplating solution is composed of chromic anhydride: 250g / L, sulfuric acid: 2g / L, lanthanum nitrate: 5g / L, and the current density is 15A / dm 2 , the electroplating time is 9s, and the single-side coating thickness is 0.5μm. After the pre-plating is completed, the copper layer is electroplated on the metal chromium. The electroplating solution composition is copper sulfate: 250g / L, sulfuric acid 100g / L, and the current density is 10A / dm 2 The thickness of the single-side coating is 2μm. After washing, drying and soap dipping, the servo motor takes up the wire on the I-shaped wheel at a certain pitch.
[0041] Step 3: Drawing. Install the electroplated tungsten alloy wire on the wire-paying end of the water tank drawing machine. After multiple passes of die drawing, the alloy wire reaches the required wire diameter and obtains the final product.
[0042] Comparative Example 1 Step 1: The tungsten alloy busbar enters the ultrasonic electrolytic alkali washing tank from the pay-off end. The alkali solution is composed of sodium hydroxide, the concentration is 70g / L, the alkali solution temperature is 70℃, the alkali washing time is 5s, and the ultrasonic frequency is 25HZ. After degreasing, the tungsten alloy busbar enters the hot water and cold water secondary washing tank, and the alkali solution on the surface of the tungsten alloy busbar is completely cleaned by countercurrent. The hot water washing temperature is 60℃ and the cold water washing temperature is 25℃. After washing, the tungsten alloy busbar enters the pickling activation tank, and is etched and activated with hydrofluoric acid. The hydrofluoric acid concentration is 20%, the temperature is 25℃, and the activation time is 3s.
[0043] Step 2: After the pretreatment is completed, electroplating is performed. The copper layer is electroplated on the tungsten alloy busbar. The composition of the electroplating solution is copper sulfate: 250g / L, sulfuric acid 100g / L, and the current density is 10A / dm 2 The thickness of the coating on one side is 2µm. After washing, drying and soap dipping, the servo motor takes up the wire on the I-shaped wheel at a certain pitch.
[0044] Step 3: Drawing. Install the electroplated tungsten alloy wire on the wire-paying end of the water tank drawing machine. After multiple passes of die drawing, the alloy wire reaches the required wire diameter and obtains the final product. Example
[0045] Step 1: The tungsten alloy busbar enters the ultrasonic electrolytic alkali washing tank from the pay-off end. The alkali solution is composed of sodium hydroxide, the concentration is 70g / L, the alkali solution temperature is 70℃, the alkali washing time is 5s, and the ultrasonic frequency is 25HZ. After degreasing, the tungsten alloy busbar enters the hot water and cold water secondary washing tank, and the alkali solution on the surface of the tungsten alloy busbar is completely cleaned by countercurrent. The hot water washing temperature is 60℃ and the cold water washing temperature is 25℃. After washing, the tungsten alloy busbar enters the pickling activation tank, and is etched and activated with hydrofluoric acid. The hydrofluoric acid concentration is 20%, the temperature is 25℃, and the activation time is 3s.
[0046] Step 2: After the pretreatment is completed, self-lubricating composite coating is electroplated. First, metal chromium is pre-plated on the surface of the tungsten alloy busbar as the bottom bonding layer. The impact chromium anode is a lead-tin alloy, and the electroplating solution is composed of chromic anhydride: 250g / L, sulfuric acid: 2g / L, lanthanum nitrate: 5g / L, and the current density is 15A / dm 2 , the electroplating time is 9s, and the single-side coating thickness is 0.5μm. After the pre-plating is completed, a copper-based lubricating composite coating is electroplated on the metal chromium. The electroplating solution composition is copper sulfate: 250g / L, sulfuric acid 100g / L, and the current density is 10A / dm 2 Solid lubricating particles are molybdenum disulfide, with a particle concentration of 50g / L, a particle size of 2μm, and a single-side coating thickness of 2μm. After washing, drying, and soap dipping, the servo motor takes up the wire on the I-shaped wheel at a certain pitch.
[0047] Step 3: Drawing. Install the electroplated tungsten alloy wire on the wire-paying end of the water tank drawing machine. After multiple passes of die drawing, the alloy wire reaches the required wire diameter and obtains the final product.
[0048] Comparative Example 2.1 Step 1: The tungsten alloy busbar enters the ultrasonic electrolytic alkali washing tank from the pay-off end. The alkali solution is composed of sodium hydroxide, the concentration is 70g / L, the alkali solution temperature is 70℃, the alkali washing time is 5s, and the ultrasonic frequency is 25HZ. After degreasing, the tungsten alloy busbar enters the hot water and cold water secondary washing tank, and the alkali solution on the surface of the tungsten alloy busbar is completely cleaned by countercurrent. The hot water washing temperature is 60℃ and the cold water washing temperature is 25℃. After washing, the tungsten alloy busbar enters the pickling activation tank, and is etched and activated with hydrofluoric acid. The hydrofluoric acid concentration is 20%, the temperature is 25℃, and the activation time is 3s.
[0049] Step 2: Electroplating is performed after pretreatment. First, metal chromium is pre-plated on the surface of the tungsten alloy busbar as the bottom bonding layer. The impact chromium anode is a lead-tin alloy, and the electroplating solution is composed of chromic anhydride: 250g / L, sulfuric acid: 2g / L, lanthanum nitrate: 5g / L, and the current density is 15A / dm 2, the electroplating time is 9s, and the single-side coating thickness is 0.5µm. After the pre-plating is completed, the copper layer is electroplated on the metal chromium. The electroplating solution composition is copper sulfate: 250g / L, sulfuric acid 100g / L, and the current density is 10A / dm 2 , the single-side coating thickness is 2µm.
[0050] Step 3: Drawing, install the electroplated tungsten alloy wire on the wire pay-off end of the water tank drawing machine, and the alloy wire reaches the required wire diameter after multiple die drawing; Comparative Example 2.2 Step 1: The tungsten alloy busbar enters the ultrasonic electrolytic alkali washing tank from the pay-off end. The alkali solution is composed of sodium hydroxide, the concentration is 70g / L, the alkali solution temperature is 70℃, the alkali washing time is 5s, and the ultrasonic frequency is 25HZ. After degreasing, the tungsten alloy busbar enters the hot water and cold water secondary washing tank, and the alkali solution on the surface of the tungsten alloy busbar is completely cleaned by countercurrent. The hot water washing temperature is 60℃ and the cold water washing temperature is 25℃. After washing, the tungsten alloy busbar enters the pickling activation tank, and is etched and activated with hydrofluoric acid. The hydrofluoric acid concentration is 20%, the temperature is 25℃, and the activation time is 3s.
[0051] Step 2: Electroplating is performed after pretreatment. First, metal chromium is pre-plated on the surface of the tungsten alloy busbar as the bottom bonding layer. The impact chromium anode is a lead-tin alloy, and the electroplating solution is composed of chromic anhydride: 250g / L, sulfuric acid: 2g / L, lanthanum nitrate: 5g / L, and the current density is 15A / dm 2 , the electroplating time is 9s, and the single-side coating thickness is 0.5µm. After the pre-plating is completed, the copper layer is electroplated on the metal chromium. The electroplating solution composition is copper pyrophosphate: 300g / L, potassium pyrophosphate 100g / L, and the current density is 8A / dm 2 , the single-side coating thickness is 2μm.
[0052] Step 3: Drawing, install the electroplated tungsten alloy wire on the wire pay-off end of the water tank drawing machine, and the alloy wire reaches the required wire diameter after multiple die drawing; Figure 4 , Figure 5 Corresponding to Example 1 and Comparative Example 1 respectively, Figure 4 and 5 It can be seen that after the metal chromium layer is pre-plated in Example 1, the coating has good bonding strength with the tungsten alloy wire substrate, and there is no coating peeling after knotting. In Comparative Example 1, the metal chromium layer is not pre-plated, and the bonding strength between the coating and the tungsten alloy wire substrate is poor. After knotting, the coating peeling phenomenon is obvious.
[0053] The tungsten alloy wires prepared in Example 2 and Comparative Examples 2.1 and 2.2 were drawn, and the experimental results are shown in Table 1: Table 1 Tungsten alloy wire drawing test results prepared in Example 2 and Comparative Examples 2.1 and 2.2 Mold specifications (μm) 56 52 49 45 42 39 37 35 33 31 Example 2 Mould usage mileage 975 983 967 988 935 946 831 835 867 889 Comparative Example 2.1 Mould Use Kilometers 986 956 946 953 943 985 346 378 397 339 Comparative Example 2.2 Mold Use Kilometers 946 953 958 912 934 948 348 365 346 359 According to the test results in Table 1, the tungsten alloy wire with a single coating such as a direct electroplated copper layer can be drawn for 400 km. The aperture of the last four dies will gradually increase and cannot be used any more. However, the tungsten alloy wire with a self-lubricating composite coating of the present invention can be drawn for more than 800 km by the last four dies, which can effectively reduce the die loss. The die usage mileage refers to the maximum length of the metal wire that can be drawn by each die when the die aperture remains unchanged.
[0054] Finally, it should be noted that the above is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.
Claims
1. A tungsten alloy wire, characterized in that: The invention is composed of a tungsten alloy busbar and a self-lubricating composite coating, wherein the self-lubricating composite coating is composed of a pre-coating layer and a composite coating from the inside to the outside.
2. The tungsten alloy wire according to claim 1, characterized in that: The wire diameter of the tungsten alloy wire is 10-200µm, and the tensile strength is above 3000MPa.
3. The tungsten alloy wire according to claim 1, characterized in that: The pre-plating layer is a metal chromium plating layer with a single-side thickness of 0.1-1µm; the composite plating layer is a metal-based composite plating layer with a single-side thickness of 0.1-5µm.
4. The tungsten alloy wire according to claim 3, characterized in that: The metal-based composite coating contains a solid lubricant, and the content of the solid lubricant in the metal-based composite coating is 0.1-10 wt %.
5. The tungsten alloy wire according to claim 4, characterized in that: The solid lubricant is composed of 0-100 wt% of metal compounds, 0-100 wt% of inorganic substances and 0-100 wt% of organic substances, wherein the metal compounds include one or more of metal oxides, metal halides, metal sulfides and metal selenides; the inorganic substances are one or more of graphite, graphite fluoride and hexagonal boron nitride; and the organic substances are one or more of polytetrafluoroethylene, polyimide, nylon, polyethylene and melamine urate.
6. A tungsten alloy wire product, characterized in that: The tungsten alloy wire is obtained by processing the tungsten alloy wire according to any one of claims 1 to 5.
7. A method for preparing a tungsten alloy wire, characterized in that: The following steps are involved: Step 1: Pre-treat the tungsten alloy busbar; Step 2: electroplating, placing the tungsten alloy busbar obtained in step 1 in an electroplating tank for pre-plating of the bottom metal coating, and then electroplating the composite coating in the electroplating tank. After the electroplating is completed, the tungsten alloy busbar is washed and soap-soaked, and then wound onto the I-shaped wheel; Step 3: Drawing. Install the tungsten alloy wire obtained in step 2 at the wire-paying end of the water tank drawing machine. The tungsten alloy wire can reach the required wire diameter after multiple drawing passes.
8. The method for preparing tungsten alloy wire according to claim 7, characterized in that: The detailed steps of the pre-treatment in step 1 are: Step A, placing the tungsten alloy busbar in an ultrasonic electrolytic alkali cleaning tank for cleaning, wherein the alkali solution comprises one or more of sodium hydroxide, sodium carbonate, and trisodium phosphate, wherein the alkali solution concentration is 50-150 g / L, the temperature is 50-80° C., the degreasing time is 1-5 s, and the ultrasonic frequency is 10-100 Hz; Step B, two-stage water washing, using countercurrent water washing method, after degreasing, the tungsten alloy busbar first enters the hot water washing tank, the water temperature is 50-70℃, the time is 1-5S, and then passes through the cold water washing tank; Step C: Activate the surface of the tungsten alloy busbar with concentrated hydrochloric acid or hydrofluoric acid at a temperature of 10-30°C for 1-5 seconds, and then wash with water for activation.
9. The method for preparing tungsten alloy wire according to claim 7, characterized in that: The process of pre-plating the bottom metal layer in step 2 is: the current density is 4-20A / dm 2 , the electroplating time is 1-30S; the anode is a lead-tin alloy or a platinum-iridium anode; the electroplating solution composition is chromic anhydride: 100-400g / L, sulfuric acid 1-5g / L, La 3+ : 0.1-2.5g / L.
10. The method for preparing tungsten alloy wire according to claim 7, characterized in that: The process of electroplating the composite coating in step 2 is as follows: the electroplating solution composition is 250g / L of one or more of metal oxides, metal halides, metal sulfides, metal selenides, 100g / L of sulfuric acid, and 0.1-100g / L of solid lubricant; the current density is 8-10A / dm 2 .
Citation Information
Patent Citations
Self-lubricating diamond wire and production method thereof
CN107378814A
Tungsten wire and elastic component
CN110871649A
Diamond wire busbar and preparation method thereof
CN118254294A
Electrolytically deposited hard chronium coatings
US4846940A
Cited By
Lubricating method for plastic forming of niobium-tungsten alloy
CN120174435A
A lubrication method for plastic forming of niobium-tungsten alloy
CN120174435B